A Japanese concept of considerations for evaluation of dental materials for tooth bleaching - Michiko Kurauchi; Yuchi Sato; Hiroyuki Tanishiro; Ryosuke Morita; Masayuki Otsuki; Jun Kaneko; Tomoyuki Tsubaki; Bunsaku Yoshida; Kota Aso; Madoka Murakami; Masuo Kondoh (Elsevier, 2023)
Recent advances in bleaching technology, such as bleaching ingredients, have accelerated the development of tooth whitening materials to change the color of natural teeth toward a lighter or whiter shade. Some bleaching materials are used for patients in combination with auxiliary medical devices to activate the bleaching materials by a light or heat source. Bleaching ingredients can be a poisonous and deleterious substance. Some bleaching materials are used in dental offices and the others at home. In clinical development of bleaching materials, appropriate evaluation of safety and efficacy is required according to the intended use. For appropriate and swift approval of the emerging bleaching materials, guideline on evaluation of dental whitening materials was discussed in a commissioned project by the Ministry of Health, Labour and Welfare of Japan for FY2021. Here, we summarize the current principles of the premarketing evaluation of the safety and efficacy.